“The heart in a bag”: The lived experience of patient-caregiver dyads with left ventricular assist device during cardiac rehabilitation - Rapelli, Giada; Giusti, Emanuele Maria; Donato, Silvia; Parise, Miriam; Pagani, Ariela Francesca; Pietrabissa, Giada; Bertoni, Anna; Castelnuovo, Gianluca (Frontiers in Psychology, 2023)
Objective. The Left Ventricular Assist Device (LVAD) has increasingly become a primary therapeutic option for longer-waiting heart transplant lists. Although survival rates are growing, the device requires complex home care. Therefore, the presence of a caregiver trained in the LVAD management is important for the success of the therapy. The LVAD leads both patients and their caregivers to experience new challenges and adapt to new lifestyle changes and limitations – but their subjective beliefs before home management remained little explored. Design. This study identified, using a phenomenological hermeneutic approach, the main components of the LVAD experience of six patient-caregiver dyads interviewed during cardiac rehabilitation. Results. We identified 4 master themes: Being between life and death, Being human with a heart of steel, Sharing is caring (and a burden), and Being small and passive. Conclusion. The knowledge from this study can be used as a guide for healthcare providers in counseling LVAD recipients and their caregivers.